2019
DOI: 10.1021/acs.jafc.9b02645
|View full text |Cite
|
Sign up to set email alerts
|

Deposition, Distribution, Metabolism, and Reduced Application Dose of Thiamethoxam in a Pepper-Planted Ecosystem

Abstract: To decrease the application dose of thiamethoxam (TMX) to control the pepper whitefly (Bemisia tabaci Q), the deposition, dissipation, metabolism, and field efficacy of TMX were investigated in a pepper (Capsicum annuum var. grossum)planted ecosystem using eight types of nozzles at six concentrations (56.25, 41.25, 26.25, 21.0, 15.75, and 10.5 g a.i./hm 2 ). The initial deposition amount of TMX in the pepper plant first increased and then decreased with increasing application dose. The optimum spray conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…It was reported that the dissipation rate of TMX depended on a variety of factors, including soil characteristics, pH values, application dose, climatic or cultivation conditions, microorganisms, organic fertilizer use, and so on [ 32 , 33 ]. The half-lives of TMX vary from 3.9 d to 94.1 d, or even longer periods, in different soil types and plant ecosystems such as pepper, citrus, tobacco, and Swiss chard [ 22 , 34 , 35 ]. The persistence of TMX in soil can be affected by introducing organic amendments such as biochar and microbial activity to accelerate degradation by Pseudomonas and Bacillus [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the dissipation rate of TMX depended on a variety of factors, including soil characteristics, pH values, application dose, climatic or cultivation conditions, microorganisms, organic fertilizer use, and so on [ 32 , 33 ]. The half-lives of TMX vary from 3.9 d to 94.1 d, or even longer periods, in different soil types and plant ecosystems such as pepper, citrus, tobacco, and Swiss chard [ 22 , 34 , 35 ]. The persistence of TMX in soil can be affected by introducing organic amendments such as biochar and microbial activity to accelerate degradation by Pseudomonas and Bacillus [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…The residual CHL and CYN detected from plants suggest plant root uptake and transport of these pesticides, although their amounts in plants tended to decrease through the cultivation period. Similarly, the distribution of insecticides in plant parts decreased with an increased pesticide exposure period [ 1 , 25 , 26 ]. Although our study did not focus on the metabolites of CHL and CYN, there are reports that the amount of metabolites relative to the parental compound (CYN) increased [ 1 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mei et al found in their study on thiamethoxam for controlling white powdery mildew in peppers that the appropriate dilution level significantly impacts the deposition of the solution on leaf surfaces, and both over-dilution and under-dilution are not conducive to the deposition of the solution on leaf surfaces. 22 In their study on fungal infection of wheat, Song et al found that slightly diluted solutions are difficult to wet and tend to rebound from the leaf surface. 23 Given this, pesticide carriers can effectively improve the effective deposition of droplets on leaf surfaces.…”
Section: Introductionmentioning
confidence: 99%